A Preliminary Outcome Study of Brief Cognitive Therapy for Management of Suicidal Thoughts and Behaviors: An Open-label Trial Protocol - Swarnalakshmi S; Munivenkatappa Manjula; Venkata Senthil Kumar Reddi (Indian Journal of Psychological Medicine)
Background: Suicidal thoughts and behaviors (STBs) are a major concern in India, but there is limited research on effective interventions. Cognitive Therapy for Suicidal Patients (CT-SP) has shown promise, but its implementation in India needs further investigation. Novelty: This study adopts a transdiagnostic approach to suicidality, recognizing the strong link between various mental health conditions and STBs. The study aims to use an evidence-based intervention for acute suicidal risk and understand its outcomes in the Indian context using systematic implementation. The blended delivery format of the intervention (both in-person and online) further enhances its relevance for diverse clinical settings. Objectives: The study aims to assess the effectiveness of a brief CT-SP intervention in reducing the severity of suicidal ideation and behaviors. Secondary objectives include evaluating changes in emotional regulation, cognitive flexibility, hopelessness, depression, anxiety, problem-solving skills, frequency of dysfunctional cognitions, and overall functioning. Methods: The study will use an open-label, single-group design with baseline, post-intervention, and follow-up assessments at one, three, and six months. Patients with recent suicidal ideation or behaviors will be recruited across diagnoses. The intervention consists of a ten-session CT-SP protocol delivered in a blended format over five weeks. Expected Outcome: The study would contribute to the empirical understanding of suicide risk management in clinical settings and inform the development of culturally relevant interventions specific to the Indian context.